Non-pharmacological intervention for shift nurses’ sleep: systematic review and meta-analysis - A Y L Lee; L A Tse (Occupational Medicine, 2026)
Abstract Background Nurses working rotating shifts often experience poor sleep quality due to circadian rhythm disruption. Previous reviews primarily focused on managerial changes to improve nurses’ alertness during night shifts. Although some studies found that individual-level non-pharmacological interventions may significantly alleviate sleep problems, past reviews focused only on aromatherapy. Aims To understand current trends and synthesise the effectiveness of non-pharmacological interventions for improving shift nurses’ sleep quality. Methods A systematic review and meta-analysis were performed using seven databases for experimental trials published from 2014 to 2024 examining the effectiveness of non-pharmacological interventions on improving shift nurses’ sleep quality. The methodological quality of the included studies was assessed by Cochrane Risk of Bias 2 (RoB 2) tool. Meta-analysis was performed under fixed or random effect model according to heterogeneity assessed by I2 statistics. Sensitivity analysis and subgroup analysis were also conducted. Results A total of 15 articles were included in the narrative synthesis, and 11 of them were included in the meta-analysis. Mindfulness programs were the most common intervention, followed by aromatherapy. Overall pooled analyses of 11 studies showed a significant improvement in shift nurses’ sleep quality with a standardised mean difference (SMD) of −0.63 (95% CI −1.01 to −0.25; P = 0.001; X2 = 71.53; I2 = 86%; P < 0.00001). Mindfulness programs were found to be beneficial, but no significant improvement was noted for aromatherapy. Conclusions Non-pharmacological interventions could effectively improve shift nurses’ sleep quality. Mindfulness programs are gaining popularity and were shown to be beneficial but need to be further improved with personalised counselling to improve compliance with irregular work schedules.